Kleopatra VII we współczesnej kulturze popularnej: przekaz źródeł czy stereotyp postrzegania Egiptu? - Kulpa, Karolina (Studia Europaea Gnesnensia, 2010)
For more than two thousand years Cleopatra has been an inspiration of artists. At the turn of the 20th and 21st century she became one of the icons of our (European) perception of Egypt. She is certainly better known than the builders of pyramids or Ramesses the Great, and she is remembered better than the names of ancient rulers. One may even venture to claim that although little is known, she is a familiar, not to say clichéd figure. One needs to consider what hides behind the representations of Cleopatra we encounter everyday in various aspects of popular culture—advertising, products of daily use, television. In my opinion, we only perceive the picture contrived by Octavian and the writers devoted to him—a femme fatale of the antiquity, an ambitious and ruthless temptress. Horace, Propertius, Florus and Pliny conveyed in their works an image of Cleopatra which met Octavian Augustus’ expectations: of a woman defeated in the eyes of the victor. A cursory read of their works in the 18th century, in the wake of renewed interest in antiquity following the discovery of Pompeii and Herculanum, led to uncritical repetition of Cleopatra’s depiction—first, in the historiography, and then in popular culture. Stereotypes concerning Egypt developed, reinforced by the descriptions of travelers. In the light of the latter, the country appears a quintessence of the Orient, with all its riches and delights. The figure of the last queen of ancient Egypt suited such notion perfectly. The most interesting issue is that today, when through archeological and historical research Cleopatra’s life became known in greater detail, the popular culture, advertising and cinematography in particular, keeps on perpetuating the stereotypical representation of this extraordinary woman. I incline towards the views of M. Krajewski, who claims that popular culture has become a lens sifting reality, and in striving to become an integral element of reality, it selects whatever is helpful (discarding the rest). The answer to the question of whether the image of Cleopatra originates from sources or stems from our stereotypes of Egypt, is, I think, a complex one. It was precisely the superficial reading of sources rediscovered, as it were, in the 18th century, that brought forth the stereotypes, whose reverberations in popular culture of the 20th and the 21st century created a specific picture of the last Egyptian queen. The “present–day” picture of Cleopatra is in a way a remote echo of Augustian propaganda, whose charm still holds sway over us. I wished to demonstrate this dependence by showing various aspects of popular culture, from press to cosmetics. Popular culture adopted those features of Cleopatra that help sell merchandise—youth, amorous intrigue, alleged beauty and murder. We cannot escape the influence she exerts on us and our lives, yet what lies beneath the facade of a pretty face with a ureus-adorned temples deserves consideration. In the case of Cleopatra VII it is a fascinating history of life and death of one of the most influential women of her times.